Political Economy of Cross-Strait Relations - Ekaterina Oganesovna Nakhatakyan (Vestnik RUDN. International Relations, 2021)
The article provides a comprehensive analysis of the interrelation of political and economic factors in Cross-Strait relations. The main political factor considered in the study is the policy of the ruling party in Taiwan towards the Mainland, its acceptance of Beijings One China policy and 1992 Consensus, put forward by Mainland China as a political basis for building Cross-Strait dialogue between the parties. Key economic factors include economic cooperation and exchanges between the two sides in such fields as bilateral trade, international capital flows and tourism. The relevance of the study refers to the settlement of the so-called Taiwan issue and the implementation of the complete reunification of the Peoples Republic of China that embodies one of the fundamental interests of Mainland China. The aim of the research is to examine the impact of political cycle in Taiwan on the economic cooperation between Beijing and Taipei, the further intensification of which could lead to the peaceful reunification through economic integration. The study provides a broad overview of the development of relations between Taiwan and Mainland China, focusing on the policies of the Taipei administrations from 1949 to 2019 and its impact on economic cooperation between the two sides. The methodological framework of the paper is mainly based on international political economy. The results of the research suggest that political cycle in Taiwan has almost no impact on Cross-Strait trade and investment. Meanwhile it has quite significant influence on Cross-Strait tourism, especially from the PRC, as it has the administrative means of regulation of the number of Mainland tourists wishing to visit Taiwan.